Tracing the Historical Development of Architecture in Cyprus and its Resilience to Seismic Hazards - Xekalakis, Georgios; Christou, Petros (International Journal of Architectural Engineering Technology, 2023)
Cyprus is an island nation in the eastern Mediterranean Sea, with a rich and varied history of architecture. Located within a seismically active zone, Cyprus has experienced a number of earthquakes over the centuries, with some of them being particularly destructive. This initiative examines the evolution of architecture in Cyprus from 1489 to present, and how this evolution is related to seismic risk. Specifically, the work will register structural elements by time period, and analyze how these elements contribute to seismic response. Further it will explore the development of architecture in Cyprus, from the Venetians to the Ottoman Empire to the British Colonial period, the Greek-Cypriot period, and the modern era, and the structural elements of each time period. The paper describes how the structural elements of each time period affect seismic risk, and what modifications may be necessary in order to improve seismic risk in Cyprus. This paper will provide useful insight into the evolution of architecture in Cyprus and its effects on seismic risk.